Preweaning nutrient supply improves lactation productivity and reduces the risk of culling in Holstein cows - L.N. Leal; J.B. Daniel; J. Doelman; B.R. Keppler; M.A. Steele; J. Martín-Tereso (Journal of Dairy Science)
ABSTRACT: This study aimed to investigate the effects of preweaning nutrient intake on milk production in the 2 first lactations, risk of culling, and metabolomic profiles of dairy cows fed a restricted (RES) or an elevated (ELE) milk supply preweaning. A total of 86 female Holstein Friesian calves were randomly assigned to either 5.4 Mcal of ME in 8 L of milk replacer (MR) per day (ELE) or 2.7 Mcal of ME in 4 L of MR per day (RES) from d 2 after birth until they were stepped down by 50% from d 42 to d 49 and fully weaned at d 50. Starting from d 50, animals from both treatment groups were fed and managed in the same way, with treatments being blinded, for the entire study duration. At 60 DIM in the first lactation, blood samples were taken for metabolomic analysis. Heifers fed the ELE diet exhibited higher ADG (0.79 vs. 0.49 kg/d) in the preweaning period, leading to higher BW at 70 d of age (94 vs. 85 kg). In the first lactation, cows fed the ELE diet preweaning exhibited higher DMI (+0.7 kg/d), higher milk fat yield (+50 g/d), and higher milk fat content (+0.24%) but lower feed efficiency (−0.04) than cows in the RES group. In the second lactation, fat- and protein-corrected milk yield (+1.8 kg/d), milk fat yield (+115 g/d), milk fat content (+0.22%), and feed efficiency (+0.06) were all higher in ELE cows. Throughout these 2 lactations, ELE cows were leaner, as indicated by a lower BCS. Cows fed the ELE diet preweaning had a higher first-service conception rate during the second lactation than cows fed the RES diet (40.7% vs. 13.0%). Moreover, the likelihood to be culled before third, fourth, or fifth calving was halved when calves were fed ELE compared with RES. Metabolomic profiling revealed distinct metabolomic profiles at 60 DIM in response to preweaning milk supply. The major metabolic pathways affected by preweaning nutrient supply at 60 DIM were pyrimidine, sphingosine, guanidino, acetamido, and purine metabolism and the tricarboxylic acid cycle. The metabolic profile differences between the groups describe a metabolic configuration that was sustained into adulthood and that may explain the improved productivity and resilience of cows fed a greater milk supply during the preweaning period.